2018
DOI: 10.1002/pc.24960
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Applications of Polysulfone/Polyimide Nanocomposite Membrane Reinforced with Silica Nanoparticles

Abstract: We synthesized polysulfone/polyimide nanocomposite membranes by solution casting method and reinforced with silica nanoparticles by in situ and ex situ techniques. Physical characteristics of nanocomposite membranes were explored by using X‐ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. The appropriate ratio of polysulfone and polyimide was revealed through structural analysis. Thermal analysis revealed highest degradation temperature of 580°C for silica reinforced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…By regulating the weight percentage of silicon element, PAIS surfaces with different silicon element density were obtained. Consistent with the previous report, the incorporation of silicon element density could obviously reduce thermal stability of PAI 27,28 and improve the strength of polyimide or co‐polyimide matrix 29–32 . The thermal stability of the PAIS decreases with the addition of silicon element, which may be due to the introduction of flexible segment CH 2 CH 2 CH 2 , at the end of polymer molecular weight when PAI is modified by a silane coupling agent (APTES), which increases molecular chain flexibility and decrease in thermal properties.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…By regulating the weight percentage of silicon element, PAIS surfaces with different silicon element density were obtained. Consistent with the previous report, the incorporation of silicon element density could obviously reduce thermal stability of PAI 27,28 and improve the strength of polyimide or co‐polyimide matrix 29–32 . The thermal stability of the PAIS decreases with the addition of silicon element, which may be due to the introduction of flexible segment CH 2 CH 2 CH 2 , at the end of polymer molecular weight when PAI is modified by a silane coupling agent (APTES), which increases molecular chain flexibility and decrease in thermal properties.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with the previous report, the incorporation of silicon element density could obviously reduce thermal stability of PAI 27,28 and improve the strength of polyimide or co-polyimide matrix. [29][30][31][32] The thermal stability of the PAIS decreases with the addition of silicon element, which may be due to the introduction of flexible segment tion, but some unreacted silicon hydroxyl groups are retained (Figure S1). As a result, the surface of the silica prepared by the solgel technology still has a hydrophilic hydroxyl group to be hydrophilic.…”
Section: Effects Of Pais On Skin Tissue Reaction In Vivomentioning
confidence: 99%
“…One example of thermoplastic polymer with convenient characteristics for the abovementioned applications is polysulfone, PSF. It has good thermal and chemical stability and high mechanical strength [20,21]. Besides, PSF is biocompatible and has been used for bio-related applications such as bone prosthetic material in orthopedics and implants, with promising results in animal models [22] or in dentistry applications [23].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Among the modification methods, blending with nanoparticle has garnered great interest owing to particle stable properties. [4,[21][22][23] Nanoparticles can be employed as nucleating agents to increase crystallinity and improve membranes morphology and pore structure, leading to influence the surface properties of the membranes. [24][25][26] In the previous study, Cui et al [27] reported that the introduction of SiO 2 resulted in an increase in the nucleation density of the polymer and thus showed a benefit for permeability of the membrane.…”
Section: Introductionmentioning
confidence: 99%